The F(0)F(1)-ATP Synthase Complex Contains Novel Subunits and Is Essential for Procyclic Trypanosoma brucei - Zíková, Alena (Public Library of Science, 2009)

(untitled)
The mitochondrial F(0)F(1) ATP synthase is an essential multi-subunit protein complex in the vast majority of eukaryotes but little is known about its composition and role in Trypanosoma brucei, an early diverged eukaryotic pathogen. We purified the F(0)F(1) ATP synthase by a combination of affinity purification, immunoprecipitation and blue-native gel electrophoresis and characterized its composition and function. We identified 22 proteins of which five are related to F(1) subunits, three to F(0) subunits, and 14 which have no obvious homology to proteins outside the kinetoplastids. RNAi silencing of expression of the F(1) α subunit or either of the two novel proteins showed that they are each essential for the viability of procyclic (insect stage) cells and are important for the structural integrity of the F(0)F(1)-ATP synthase complex. We also observed a dramatic decrease in ATP production by oxidative phosphorylation after silencing expression of each of these proteins while substrate phosphorylation was not severely affected. Our procyclic T. brucei cells were sensitive to the ATP synthase inhibitor oligomycin even in the presence of glucose contrary to earlier reports. Hence, the two novel proteins appear essential for the structural organization of the functional complex and regulation of mitochondrial energy generation in these organisms is more complicated than previously thought.